EVOLUCIÓN HISTÓRICA DE LA LEX MERCATORIA - Parra Rivera, Rose Mary (2010)
It is investigated the historical evolution of a new juridical order that regulates the internacional business transactions, by means of the formalization of uses and prevailing principles. This is what is named in Private International law, Lex Mercatoria, who is the right arisen from the commercial activity without state intervention, and whose legitimacy is obtained by recognition of the users.